Method for evaluating impulsive shear and residual capacity behavior of bolted connections - Sanborn, M.; Stewart, L.K. (Engineering structures, 2020)
•Developed experimental method to evaluate impulsive behavior of steel components.•Developed method to quantify the in situ residual capacity behavior of the damaged components.•Validated the repeatability of the new experimental method.•Provided experimental protocol for recreation of experimental method. When structures are subjected to blast, shock, and other impulsive events, the potential for progressive collapse of the structure due to the loss of load bearing members is a significant concern. An understanding of the behavior of bolted connections during and after impulsive events is necessary to predict and prevent collapse of the structure. Relatively little experimental research has been conducted to investigate the behavior of such components subjected to impulsive shear and no experimental studies have evaluated the residual shear capacity of bolts or bolted connections after an impulsive event, which represent the ability to continue carrying gravity design loads. To fill this gap in knowledge, an experimental method was developed to subject bolts and bolted connections to an impulsive shear event and then measure the residual static capacity of the bolt in situ after the event. In the developed methodology, impulsive loads were generated through the use of a high-speed hydraulic actuator to accelerate a flyer mass to a desired impact velocity towards an impulsive shear apparatus, which holds the bolt. A system was designed to be installed within the impulsive setup to apply a quasi-static load after the impulsive event. A small experimental series was conducted using a conservative, low-friction bolted interface to validate the experimental setup and provide initial insights into bolt behavior for modeling purposes. The series of structural bolt experiments under impulsive loads focused on exploring three aspects: 1) the rigidity of the bolts under impulsive loads as compared to static loading conditions; 2) the appropriateness of static and dynamic increase factors under impulsive shear loads for structural bolts; and 3) the characterization of bolt damage in terms of permanent shear deformation as the result of an impulsive loading.